2015
DOI: 10.1159/000381318
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Chemotherapy-Induced Neutropenia with the Biosimilar Filgrastim: A Non-Interventional Observational Study of Clinical Practice Patterns

Abstract: Background: Biosimilars are similar but non-identical versions of existing biological drugs. The HEXAFIL study was an observational study that assessed the clinical usage, safety and efficacy of the biosimilar filgrastim in routine clinical practice in Germany. Patients and Methods: A total of 1,337 cancer patients received the biosimilar filgrastim for primary prophylaxis (PP), secondary prophylaxis (SP) or interventional treatment (TX) plus chemotherapy. Data including neutropenic complications and adverse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
5
15
0
Order By: Relevance
“…During the first cycle of chemotherapy, only 1.8% of patients experienced FN. Tolerance and safety of biosimilar filgrastim was similar to that previously known for this class of drugs; that is, bone and muscle pain were the most common treatment-related adverse events (12).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…During the first cycle of chemotherapy, only 1.8% of patients experienced FN. Tolerance and safety of biosimilar filgrastim was similar to that previously known for this class of drugs; that is, bone and muscle pain were the most common treatment-related adverse events (12).…”
Section: Discussionsupporting
confidence: 65%
“…The frequency of neutropenia of all grades and grade 4 neutropenia (ANC <0.5x10 3 /µl) were comparable for biosimilar filgrastim and original products (Granulokine ® and Neupogen ® ; Amgen Inc.) (15). Similarly, the incidence of FN did not significantly differ with the biosimilar drug compared to the originators; the incidence was 44% for biosimilar filgrastim and 40% for the original filgrastim (12). On the basis of the present study, it was concluded that biosimilar filgrastim is effective in the prevention of FN and reduces the frequency of unplanned hospitalization in patients with soft tissue sarcomas (15 ) was also found in a non-interventional study (16), in which 77 patients with cancer were treated with biosimilar filgrastim and 25 were treated with the original product.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations